Cerebrospinal fluid assessment in dogs with spinal tumors and intervertebral disk herniation - Lipar, Marija (Array, 2020)
The study presents a retrospective case study. This aim was to determine whether lactate, glucose and total protein in serum and cerebrospinal fluid (CSF) can be used as specific biochemical markers for rapid differential diagnosis between intervertebral disk herniation and spinal tumors. Canine blood (n=9) and cerebrospinal fluid (n=9) were collected for chemistry analysis in nine dogs divided into two groups: intervertebral disk herniation group (IVDHG) (n=6) and spinal tumor group (TG) (n=3). Absorption spectrophotometry was used for quantitative determination of the concentrations of lactate, glucose and total protein in serum and CSF. Lactate concentration in serum and CSF and glucose concentration in CSF were 40-60% higher in subjects in TG compared to the IVDHG group. Serum lactate concentrations in the IVDHG group were 60% lower than physiological values. The results indicate that elevated concentration of glucose, lactate and total proteins in CSF and serum are indicative of a tumor, while a decrease of serum lactate and other parameters within normal range indicate disk herniation.